Divorce in Islam: Legal, Social, and Ethical Perspectives - Audu, Hassan; Muktar, Abdulmutalib (NIU Journal of Humanities, 2025)
This paper investigates divorce (talaq) in Islam by discussing legal aspects, social implications and ethical dimensions. Based on Classical Islamic Jurisprudence (fiqh), modern legal theories and empirical research, this book examines the complexities of role-relations between the husband and wife in various Muslim environments and countries. The study finds marked differences in divorce process and gender-based guidelines and social consequences among the various religious-legal traditions of Islam and current Muslim-majority countries. From a comparative analysis of legal systems of various countries including Morocco, Egypt, Malaysia and Pakistan, this study depicts the transformation from classical jurisprudential principle to modern statutory law in divorce matters. The results suggest that although Islam allows divorce, it does so within a complex of ethical, procedural, and social restrictions intended to preserve the family while respecting individual rights. The project is situated within a wider academic debate on Islamic family law reform, gender equality and the relationship between religious authenticity and modern legal norms. Keywords: Islamic Divorce, Talaq, Islamic Family Law, Gender Equality, Jurisprudence, Muslim Societies